STUDENT’S PERCEPTION ON ENGLISH PRONUNCIATION DIFFICULTIES WORDS OF ELEVENT GRADE STUDENTS AT SMA N 3 TONDANO - Huso, Trivena; Muntuuntu, Meity; Sanger, Maikel (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The background of this research was based on the student’s perception on pronunciation difficulties. The purpose of this research is to find out perception about difficulties in pronuncing words. This study was carried out at SMA Negeri 3 Tondano. The subject of this study was the 11th grade of science departement students in the academic year of 2022/2023. This research used qualitative research through questionnaires design. The data of this research were collected by using likert scale. The result of this research showed that they exist several problems that students encounter related to pronunciation learning were difficulties in word stress, fluency, and memorizing words. The results above show that there are still many difficulties faced by students in learning pronunciation, and several solutions can be made by giving students the opportunity to tell about personal experiences to facilitate each student’s English pronunciation. They are also given the task of memorizing English words that are used every day so as to facilitate pronunciation in English